The Malay Community’s Yellow Rice Scattering Tradition in Baru Village, South Arut, West Kotawaringin - Silvana Dewi; Selvia Santi; Suryanti (Journal of Islamic History, 2025)
This research explores the yellow rice sprinkling tradition practiced by the Malay community in Kelurahan Baru, Arut Selatan, Kotawaringin Barat Regency. Originating from the pre-Islamic era, this ritual has been transformed over time through Islamic adaptation. While often mistaken as a Dayak custom, it is actually rooted in Malay traditions, shaped by local cultural interactions including elements of Dayak culture and enriched by Islamic teachings.Today, the ritual is typically performed during significant events such as weddings, religious ceremonies, and welcoming guests. Though its outward form has evolved, it retains deep symbolic meaning, representing prayers for protection, well-being, and gratitude. The practice now often includes Islamic elements like sholawat (praises for the Prophet) and intentions directed to Allah SWT, highlighting its religious integration.This qualitative study investigates how the ritual is conducted and its meanings within the community. Data were collected through in-depth interviews with community elders, religious leaders, and local residents. The findings show that the ritual is still carried out with a sense of sacredness, usually by respected cultural figures, and is often combined with the tampung tawar ceremony. Ultimately, this tradition reflects a harmonious blend of ancestral heritage and Islamic values within Malay cultural identity. REFERENCE Afriansyah, R. (2021). The Tradition of Scattering Yellow Rice and Coins in Lampung Traditional Wedding Processions: An Urf Perspective in Islamic Law (A Case Study in Mataram Marga Village, Sukadana District, East Lampung Regency). Thesis. IAIN Metro. Al Qutuby, S., & Kholiludin, T. (2020). Religion & Culture of the Archipelago Post-Islamization. Semarang: eLSA Press. Alamsyah, AG, Nugraha, A., Reza, M., Sazali, H., & Dalimunthe, MA (2022). Malay Culture and the Influence of Islam in Wedding Ceremonies in Tanjung Balai. MUKADIMAH: Journal of Education, History, and Social Sciences, 6(2), 410–413. https://doi.org/10.30743/mkd.v6i2.5532 Ani, N., Abubakar, A., & Iqbal, M. (2019). Acculturation of Islam in Dayak Ngaju Traditional Marriage: The History of the Muslim Community in Petak Bahandang Village, Katingan Regency, Central Kalimantan. Journal of the Study of Religion and Society, 15(2), 107–117. https://doi.org/10.23971/jsam.v15i2.1624 Anwar, R. (2023). Youth and the Preservation of Local Culture in the Digital Era. Journal of Social and Cultural Studies, 15(1), 55–68. Ashmarita, Jalil, A., Satria, Hartini, & Rahman, H. (2025). Duai Boe Boteh: The Ritual of the Bridal Bathing of the Bajo Ethnic Group in Waturambaha Village, Lasolo Islands District, North Konawe Regency. Journal of Fisheries Socioeconomics, 10(2), 149–156. https://doi.org/10.33772/jsep.v10i2.241 Beding, V.O., & Astuti, S. (2024). The Meaning of Symbols in the Sengkelan Kanong Tradition of the Sintang Malay Community. Journal of Indonesian Language and Literature Education, 13(1). https://doi.org/10.31000/lgrm.v13i1.11068 Bell, C. (1997). Ritual: Perspectives and Dimensions. Oxford: Oxford University Press. Bell, C. (2009). Ritual: Perspectives and Dimensions. Oxford: Oxford University Press. Efansyah, T., & Andaryuni, L. (2024). The Tradition of Sowing Yellow Rice in Wedding Processions. Attractive: Innovative Education Journal, 6(1). https://doi.org/10.51278/aj.v6i1.1140 Lailiyah, RD (2021). A Review of the 'Urf' on the Tradition of Throwing Yellow Rice at Weddings (Case Study in Karangdagangan Village, Bandarkedungmulyo District, Jombang Regency). Thesis. Unipdu Jombang. Pangaribuan, N. (2023). The Tepung Tawar Tradition: Acculturation of Islam and Malay Culture in the Malay Wedding Procession in Tanjung Balai City. Tamaddun: Journal of Islamic Culture and Literature, 23(2), 97–108. Pelu, IEAS, & Tarantang, J. (2022). Comparison of Legal Culture: Peaceful Customary Peace in South Kalimantan and Barapen in Papua. Yogyakarta: K-Media Publisher. Sarip, M. (2022). Unraveling the Meaning of the Color Yellow in the Sacred Nusantara Tradition with Limitations. Retrieved July 25, 2025, from https://kaltimkece.id/rupa/risalah/mengurai-makna-warna-kuning-dalam-tradisi-nusantara-yang-sakral-dengan-batasan Sartika, D. (2021). The Use of Yellow Rice in Death Rituals in Tanjung Keputran Village from an Islamic Faith Perspective. Thesis. UIN Raden Fatah Palembang. Suryadi, FF, & Azeharie, SS (2020). Tatung as a Culture of Chinese Society (A Study of Tatung Ritual Communication in Singkawang). Connection, 4(1), 90. https://doi.org/10.24912/kn.v4i1.6615 Wahyuni, RS, Parji, P., & Hanif, M. (2023). The Symbolic Meaning of Uborampe, the Ritual of Bathing Brides at Sendang Modo Kandangsapi Jenar, Sragen and Its Potential as a Source of Cultural Resilience. Syntax Literate; Indonesian Scientific Journal, 7(9), 15539–15558. https://doi.org/10.36418/syntax-literate.v7i9.14532 Widaty, C., & Nur, R. (2022). Bridal Bathing Ritual in Banjar Traditional Wedding Ceremonies in Martapura, South Kalimantan. Journal of Sociology and Humanities Education, 13(2), 749. https://doi.org/10.26418/j-psh.v13i2.58086 Zulkarnain, H., Linyang, T., Musa, P., & Nur, F. (2019). The Symbolic Meaning of the Tepung Tawar Tradition in Durian Sebatang Village, Seponti District, Kayong Utara Regency. Journal of Anthropology, 2(2), 133–153.